Setting degradation curves shear modulusand and damping ratio for soil ash in Armenia ( Colombia ) (Revista de Investigaciones Universidad del Quindío, 2015)
This paper proposes two models or equations based on the PI (plasticity index) to describe the degradation of normalized shear modulus and damping ratio in volcanic ash soils for the city of Armenia, the equations are derived from the dynamic tests performed at soil samples collected in the microzonation of the city. The first model is associated with ash soils, evidenced through cyclic triaxial testing to measure their dynamic properties at high strain levels. The second model is derived from the resonant column test that measures the dynamic properties of soil with low deformations. It was found that the IP is a fundamental variable in the model describing the dynamic behavior of volcanic ash, where it was shown that the lack of variable effective confinement pressure o'o in the obtained models, generate a notable difference between the curves obtained with the triaxial test model and the model of resonant column test.
Keywords: Shear modulus; Damping ratio; Plasticity index; Cyclic Triaxial; Resonant column; Volcanic Ash